1992
DOI: 10.1042/bj2840399
|View full text |Cite
|
Sign up to set email alerts
|

Purification of PKC-I, an endogenous protein kinase C inhibitor, and types II and III protein kinase C isoenzymes from human neutrophils

Abstract: Human neutrophil protein kinase C (PKC) activity is inhibited by an endogenous protein found primarily in the pellet fraction from homogenized specific granules, which was both heat- and proteinase-sensitive [Balazovich, Smolen & Boxer (1986) J. Immunol. 137, 1665-1673]. We now report that two PKC isoenzymes and the endogenous PKC inhibitor, which we named PKC-I, were purified from human neutrophils. A neutrophil soluble fraction that was subjected to DEAE-Sephacel chromatography yielded highly enriched PKC be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Endogenous inhibitors for PKCs have been isolated from rat (18) and sheep brains (19), and from neutrophils (20). An inhibitory activity has also been found in Jurkat cells (21).…”
Section: The Protein Kinases Cmentioning
confidence: 99%
“…Endogenous inhibitors for PKCs have been isolated from rat (18) and sheep brains (19), and from neutrophils (20). An inhibitory activity has also been found in Jurkat cells (21).…”
Section: The Protein Kinases Cmentioning
confidence: 99%
“…PKC inhibitors reported so far in the literature include synthetic compounds and inhibitors of biological origin. [18][19][20][21][22][23] In this paper, we showed for the first time that BSP-A1/A2 inhibits PKC activity, and the inhibition is dose dependent. Since BSP-A1/-A2, BSP-A3 and BSP-30-kDa are homologous proteins, it is reasonable to conjecture that BSP-A3 and BSP-30-kDa can also inhibit the PKC activity and further study is under way.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of endogenous PKC inhibitors has been reported in a variety of cell types and tissues (Schwantke and Le Peuch, 1984;McDonald and Walsh, 1985;Balazovich et al ., 1986;Eyster, 1990;Toker et al, 1990;Gandini et al, 1993) . Three of these inhibitors, a 17-kDa protein (McDonald and Walsh, 1985;Pearson et al ., 1990) from bovine brain called PKC inhibitor-1 (PKCI-1), a 30-kDa protein Joker et al, 1990Joker et al, , 1992 from sheep brain termed kinase C inhibitory protein-1 (KCIP-1 ), and a 41-kDa PKC inhibitor (PKC-I) from human neutrophils (Balazovich et al, 1986(Balazovich et al, , 1992 have been well characterized . Preliminary characterization of the neuroblastoma PKC inhibitor (N-KCIF) suggested that it may be different from the brain inhibitors PKCI-1 and KCIP-1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, what role, if any, KCIP-1 plays in these or any other cellular processes remains unknown . The presence of PKC-I in specific granule-containing human neutrophils and not in "resting," specific granule-deficient neutrophils has led to the speculation that PKC-I may play a role in normal neutrophil functions (Balazovich et al, 1986(Balazovich et al, , 1992 . A unique feature of the present study is the demonstration that a correlation exists between PKC and N-KCIF activities in differentiating neuroblastoma cells .…”
Section: Discussionmentioning
confidence: 99%